The Emerging Role of Non-Coding RNAs in Osteoarthritis - Ghafouri-Fard, Soudeh; Poulet, Christophe; Malaise, Michel; Abak, Atefe; Mahmud Hussen, Bashdar; Taheriazam, Afshin; Taheri, Mohammad; Hallajnejad, Mohammad (Frontiers in Immunology, 2021)
Osteoarthritis (OS) is the most frequent degenerative condition in the joints, disabling many adults. Several abnormalities in the articular cartilage, subchondral bone, synovial tissue, and meniscus have been detected in the course of OA. Destruction of articular cartilage, the formation of osteophytes, subchondral sclerosis, and hyperplasia of synovial tissue are hallmarks of OA. More recently, several investigations have underscored the regulatory roles of non-coding RNAs (ncRNAs) in OA development. Different classes of non-coding RNAs, including long ncRNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs), have been reported to affect the development of OA. The expression level of these transcripts has also been used as diagnostic tools in OA. In the present article, we aimed at reporting the role of these transcripts in this process. We need to give a specific angle on the pathology to provide meaningful thoughts on it.